Implicit differentiation

course MTH 173

11JULY2010 AT 2028

016. Implicit differentiation.

*********************************************

Question: `q001. Suppose that y is a function of x. Then the derivative of y with respect to x is y '. The derivative of x itself, with respect to x, is by the power function rule 1, x being x^1. What therefore would be the derivative of the expression x^2 y?

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

x^2 y==

2xy’+x^2y’

confidence rating #$&* 3

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

`aBy the product rule we have (x^2 y) ' = (x^2) ' y + x^2 * y ' = 2 x y + x^2 y ' .

STUDENT QUESTION

I understand this concept except for where the 2xy came from?

(x^2)' * y = 2x * y.

The derivative of x^2 with respect to x is 2x.

------------------------------------------------

Self-critique rating #$&*ent: 1

INSTRUCTOR RESPONSE

(x^2 y) ' = (x^2) ' y + x^2 * y '

The 2 x y comes from (x^2) ' y:

(x^2) ' = 2x so (x^2)' y = 2 x y.

Thus (x^2) ' y + x^2 * y ' = 2 x y + x^2 y '

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):ok

------------------------------------------------

Self-critique rating #$&*3

*********************************************

Question: `q002. Note that if y is a function of x, then y^3 is a composite function, evaluated from a given value of x by the chain of calculations that starts with x, then follows the rule for y to get a value, then cubes this value to get y^3. To find the derivative of y^3 we would then need to apply the chain rule. If we let y' stand for the derivative of y with respect to x, what would be the derivative of the expression y^3 with respect to x?

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

y^3==

[y(x)^3] ' =

xy’ * f’[y(x)]=

xy’ * 3[ y(x) ] ^2=

3y^2 (y’)

confidence rating #$&* 2

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

`aThe derivative of y^3 with respect to x can be expressed more explicitly by writing y^3 as y(x)^3. This reinforces the idea that y is a function of x and that we have a composite f(y(x)) of the function f(z) = z^3 with the function y(x). The chain rule tells us that the derivative of this function must be

(f ( y(x) ) )' = y ' (x) * f ' (y(x)),

in this case with f ' (z) = (z^3) ' = 3 z^2.

The chain rule thus gives us (y(x)^3) ' = y ' (x) * f ' (y(x) ) = y ' (x) * 3 * ( y(x) ) ^2.

In shorthand notation, (y^3) ' = y ' * 3 y^2.

This shows how the y ' comes about in implicit differentiation.

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):ok

------------------------------------------------

Self-critique rating #$&*3

*********************************************

Question: `q003. If y is a function of x, then what is the derivative of the expression x^2 y^3?

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

x^2 y^3=

(x^2*y^3)’=

(2x+y^3)+ [(x^2)(3y^2)y’]

confidence rating #$&* ok

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

`aThe derivative of x^2 y^3, with respect to x, is

(x^2 y^3) ' = (x^2)' * y^3 + x^2 * (y^3) ' = 2x * y^3 + x^2 * [ y ' * 3 y^2 ] = 2 x y^3 + 3 x^2 y^2 y '.

Note that when the expression is simplified, the y ' is conventionally placed at the end of any term of which is a factor.

STUDENT QUESTION

Ok I understand everything until the last part of the answer. How come the 3 only got combined with the x^2?

INSTRUCTOR RESPONSE

a * b * c = c * b * a = b * c * a = etc.. The order in which the quantities are listed in a string of multiplications doesn't matter.

So x^2 * [ y ' * 3 y^2 ] means the same thing as 3 y^2 * x^2 * y ' which means the same as 3 x^2 y^2 y '.

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):ok

------------------------------------------------

Self-critique rating #$&*3

*********************************************

Question: `q004. The equation 2x^2 y + 7 x = 9 can easily be solved for y. What is the result?

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

2x^2 y + 7 x = 9 solve for y

2x^2 y + 7 x = 9==

(2x^2)y=9-7x

y=(9-7x)/(2x^2)

confidence rating #$&* 3

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

`aStarting with 2 x^2 y + 7 x = 9 we first subtract seven x from both sides to obtain

2 x^2 y = 9 - 7 x. We then divide both sides by 2 x^2 to obtain

y = (9 - 7 x ) / (2 x^2), or if we prefer

y = 9 / (2 x^2 ) - 7 / ( 2 x ).

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):ok

------------------------------------------------

Self-critique rating #$&*3

*********************************************

Question: `q005. Using the form y = 9 / (2 x^2 ) - 7 / ( 2 x ), what is y and what is y ' when x = 1?

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

y = 9 / (2 x^2 ) - 7 / ( 2 x )

y’= 9/2 * (-2 / x^3) - 7/2 * (-1 / x^2)

y’= -9 / x^3 + 7 / (2 x^2)

y(1)=9/2(1^2) -7 / 2(1)=1

y’(1)= -9 / (1)^3 + 7 / [2 (1^2)]= -18/2 + 7/2 =-11/2

confidence rating #$&* 3

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

`ay ' = 9/2 * ( 1/x^2) ' - 7/2 ( 1 / x) ' = 9/2 * (-2 / x^3) - 7/2 * (-1 / x^2) = -9 / x^3 + 7 / (2 x^2).

So when x = 1 we have

y = 9 / (2 * 1^2 ) - 7 / ( 2 * 1 ) = 9/2 - 7/2 = 1 and

y ' = -9 / 1^3 + 7 / (2 * 1^2) = -9 + 7/2 = -11 / 2.

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):ok

------------------------------------------------

Self-critique rating #$&*3

*********************************************

Question: `q006. The preceding calculation could have been obtained without solving the original equation 2x^2 y + 7 x = 9 for y. We could have taken the derivative of both sides of the equation to get 2 ( (x^2) ' y + x^2 y ' ) + 7 = 0, or 2 ( 2x y + x^2 y ' ) + 7 = 0.

Complete the simplification of this equation, then solve for y ' .

Note that when x = 1 we have y = 1. Substitute x = 1, y = 1 into the equation for y ' and see what you get for y '.

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

2 ( 2x y + x^2 y ' ) + 7 = 0==

2(2xy+x^2y’)=-7== subtract 7 from both sides

(2xy+x^2y’)/2=-7/2 divided both sides by 2

2xy+x^2y’=-7/2 ==subtract 2xy from both sides

x^2y’=-7/2 -2xy== divide both sides by x^2

y’=[-7/2 -2xy]/x^2=-2y/x-7/(2x^2)

y’= -2(1/1)-7/[2x(1^2)]= -11/2

confidence rating #$&* 3

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

`aStarting with 2 ( 2x y + x^2 y ' ) + 7 = 0 we divide both sides by 2 to obtain

2x y + x^2 y ' + 7/2 = 0. Subtracting 2 x y + 7 / 2 from both sides we obtain

x^2 y' = - 2 x y - 7 / 2.

Dividing both sides by x^2 we end up with

y ' = (- 2 x y - 7 / 2) / x^2 = -2 y / x - 7 / ( 2 x^2).

Substituting x = 1, y = 1 we obtain

y ' = -2 * 1 / 1 - 7 / ( 2 * 1^2) = - 11 / 2.

Note that this agrees with the result y ' = -11/2 obtained when we solved the original equation and took its derivative. This shows that it is not always necessary to explicitly solve the original equation for y. This is a good thing because it is not always easy, in fact not always possible, to solve a given equation for y.

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary): ok

------------------------------------------------

Self-critique rating #$&*3

*********************************************

Question: `q007. Follow the procedure of the preceding problem to determine the value of y ' when x = 1 and y = 2, for the equation 2 x^2 y^3 - 3 x y^2 - 4 = 0. Also validate the fact that x = 1, y = 2 is a solution to the equation, because if this isn't a solution it makes no sense to ask a question about the equation for these values of x and y.

Your Solution:

2 x^2 y^3 - 3 x y^2 - 4 = 0== 2(1)(2^3)-3(1)(2^2)-4=16-12-4=0

4xy^3+6x^2y^2y’-6xyy’-3y^2=0

4xy^3-3y^2=-6x^2y^2y’+6xyy’==got y’ to one side

4xy^3-3y^2=(-6x^2y^2+6xy)y’==pulled out y’ on right side

(4xy^3-3y^2)/ (-6x^2y^2+6xy) = y’== divided both sides by (-6x^2y^2+6xy)

(4xy^2-3y)/ (-6x^2y+6x) = y’==reduce by y

when x=1 and y=2==y’==((4(1)4)-6)/ (-6(1)2+6)=10/-6

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):

------------------------------------------------

Self-critique rating #$&*

*********************************************

Question: `qNote that this time we do not need to solve the equation explicitly for y. This is a good thing because this equation is cubic in y, and while there is a formula (rather a set of formulas) to do this it is a lengthy and messy process.

The derivative of the equation 2 x^2 y^3 - 3 x y^2 - 4 = 0 is (2 x^2 y^3) ' - (3 x y^2) ' - (4)' = 0. Noting that 4 is a constant, we see that (4)' = 0. The derivative of the equation therefore becomes

(2 x^2) ' * y^3 + 2 x^2 * ( y^3) ' - (3 x ) ' * y^2 - 3 x * (y ^2 ) ' = 0, or

4 x y^3 + 6 x^2 y^2 y' - 3 y^2 - 6xy y' = 0. Subtracting from both sides the terms which do not contain y ' we get

6 x^2 y^2 y ' - 6 x y y ' = - 4 x * y^3 + 3 y^2. Factoring out the y ' on the left-hand side we have

y ' ( 6 x^2 y^2 - 6 x y) = -4 x y^3 + 3 y^2. Dividing both sides by the coefficient of y ':

y ' = (- 4 x * y^3 + 3 y^2) / ( 6 x^2 y^2 - 6 x y ) . The numerator and denominator have common factor y so we end up with

y' = (- 4 x * y^2 + 3 y) / ( 6 x^2 y - 6 x ).

Now we see that if x = 1 and y = 2 the equation 2 x^2 y^3 - 3 x y^2 - 4 = 0 gives us

2 * 1^2 * 2^3 - 3 * 1 * 2^2 - 4 = 0, or

16 - 12 - 4 = 0, which is true.

Substituting x = 1 and y = 2 into the equation y' = (- 4 x * y^2 + 3 y) / ( 6 x^2 y - 6 x ) we get

y ' = (- 4 * 1 * 2^2 + 3 * 2) / ( 6 * 1^2 * 2 - 6 * 1 ) =

(-16 + 6) / (12 - 6) = -10 / 6 = -5/3 or -1.66... .

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):ok

------------------------------------------------

Self-critique rating #$&*3

*********************************************

Question: `q008. (Mth 173 only; Mth 271 doesn't require the use of sine and cosine functions). Follow the procedure of the preceding problem to determine the value of y ' when x = 3 and y = `pi, for the equation x^2 sin (y) - sin(xy) = 0.

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

x^2 sin (y) - sin(xy) = 0 == 9sin(pi) –sin(3pi)==0

2xsin(y) + x^2cos(y)y’ – cos(xy) (y+xy’)== distribute cos(xy)

2xsin(y) + x^2cos(y)y’ – ycos(xy) + xcos(xy)y’=0 get y’ together on one side

2xsin(y) – ycos(xy) = -x^2cos(y)y’- xcos(xy)y’== factor out y’ on right side

2xsin(y) – ycos(xy) = [-x^2cos(y)- xcos(xy)]y’==divide both sides by[-x^2cos(y)- xcos(xy)]

y’=2xsin(y) – ycos(xy) / [-x^2cos(y)- xcos(xy)]

y’=2(3)sin(pi) – picos(3pi) / [-3^2cos(pi)- 3cos(3pi)]= subsututed x=3 and y=pi

y’=6sinpi-picos(3pi)/ [9cos(pi)- 3cos(3pi)]==approx. -.5236

confidence rating #$&* 3

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

`aTaking the derivative of both sides of the equation we obtain

(x^2) ' sin(y) + x^2 (sin(y) ) ' - ( sin (xy) ) '.

By the Chain Rule

(sin(y)) ' = y ' cos(y) and

(sin(xy)) ' = (xy) ' cos(xy) = ( x ' y + x y ' ) cos(xy) = (y + x y ' ) cos(xy).

So the derivative of the equation becomes

2 x sin(y) + x^2 ( y ' cos(y)) - ( y + x y ' ) cos(xy) = 0. Expanding all terms we get

2 x sin(y) + x^2 cos(y) y ' - y cos(xy) - x cos(xy) y ' = 0. Leaving the y ' terms on the left and factoring ou y ' gives us

[ x^2 cos(y) - x cos(xy) ] y ' = y cos(xy) - 2x sin(y), so that

y ' = [ y cos(xy) - 2x sin(y) ] / [ x^2 cos(y) - x cos(xy) ].

Now we can substitute x = 3 and y = `pi to get

y ' = [ `pi cos( 3 * `pi) - 2 * 3 sin(`pi) ] / [ 3^2 cos(`pi) - 3 cos(3 * `pi) ] = [ `pi * -1 - 2 * 3 * 0 ] / [ 9 * -1 - 3 * -1 ] = -`pi / 6.

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):

ok

------------------------------------------------

Self-critique rating #$&*3

"

&#This looks good. See my notes. Let me know if you have any questions. &#

#$&*